Cellular and transcriptome signatures unveiled by single-cell RNA-Seq following ex vivo infection of murine splenocytes with Borrelia burgdorferi - Kumaresan, Venkatesh; Ingle, Taylor MacMackin; Kilgore, Nathan; Zhang, Guoquan; Hermann, Brian P.; Seshu, Janakiram (Frontiers in Immunology, 2023)
Lyme disease, the most common tick-borne infectious disease in the US, is caused by a spirochetal pathogen Borrelia burgdorferi (Bb). Distinct host responses are observed in susceptible and resistant strains of inbred of mice following infection with Bb reflecting a subset of inflammatory responses observed in human Lyme disease. The advent of postgenomic methodologies and genomic data sets enable dissecting the host responses to advance therapeutic options for limiting the pathogen transmission and/or treatment of Lyme disease. In this study, we used single-cell RNA-Seq analysis in conjunction with mouse genomics exploiting GFP-expressing Bb to sort GFP+ splenocytes and GFPbystander cells to uncover novel molecular and cellular signatures that contribute to early stages of immune responses against Bb. These data decoded the heterogeneity of splenic neutrophils, macrophages, NK cells, B cells and T cells in C3H/HeN mice in response to Bb infection. Increased mRNA abundance of apoptosis-related genes was observed in neutrophils and macrophages clustered from GFP+ splenocytes. Moreover, complement mediated phagocytosis related genes such as c1q and Ficolin were elevated in an inflammatory macrophage subset suggesting upregulation of these genes during the interaction of macrophages with Bb-infected neutrophils. In addition, the role of DUSP1 in regulating the expression of Casp3 and pro-inflammatory cytokines Cxcl1, Cxcl2, Il1b and Ccl5 in Bb-infected neutrophils were identified. These findings serve as a growing catalog of cell phenotypes/biomarkers among murine splenocytes that can be exploited for limiting spirochetal burden to limit the transmission of the agent of Lyme disease to humans via reservoir hosts.